Implementation Of Ranger Of Active Rigid Motion To Prevent Diabetic Ulcers In Patients With Type Ii Diabetes Mellitus Through The Application Of Virginia Henderson's Theory At Rejang Lebong Regional Hospital - Repa, Alfa Rezi Septri; Kando, Berlian (Jurnal Kesehatan Mitra Sekawan, 2025)
The International Diabetes Federation (IDF) estimates that in the 20-79 age group, at least 463 million (9.3% of the total population of the same age) people suffer from diabetes mellitus in the world. Of the several conceptual models, one of them is Virginia Henderson. The purpose of this study is for the author to understand and apply the Range of Motion Active Rigid for the Prevention of Diabetic Ulcers in Type II Diabetes Mellitus Patients Through the Application of Virginia Henderson Theory at Rejang Lebong Regional Hospital. The research method used in this study is a case study which is the subject of this study which is used to explore the Application of Range of Motion Active Rigid for the Prevention of Diabetic Ulcers in Type II Diabetes Mellitus Patients Through the Application of Virginia Henderson Theory at Rejang Lebong Regional Hospital. Evaluation in Case 1 and Case 2, the problem of impaired physical mobility can be resolved so that it is concluded that the application of Range of Motion can reduce the Risk of Skin Integrity in Type II Diabetes Mellitus patients. It is hoped that Rejang Lebong Regional General Hospital will be encouraged to implement a standard protocol involving stiff active ROM exercises as part of the routine care of type II diabetes mellitus patients to prevent diabetic ulcers.